2004
DOI: 10.1111/j.1467-9922.2004.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive Evidence Versus Explicit Rule Presentation and Explicit Negative Feedback: A Computer‐Assisted Study

Abstract: The facilitative role of explicit information in second language acquisition has been supported by a significant body of research (Alanen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
123
4
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(149 citation statements)
references
References 22 publications
13
123
4
2
Order By: Relevance
“…That is, it was the structured input that helped learners to produce the targeted form, not the EI. In their similar research, Sanz and Morgan-Short (2004) found a lack of a role of EI in PI, and therefore argued that EI may not be a necessary component for PI. Or, as Doughty (2004) put it, the inclusion could be superfluous when one wants to draw attention to form.…”
Section: Discussionmentioning
confidence: 99%
“…That is, it was the structured input that helped learners to produce the targeted form, not the EI. In their similar research, Sanz and Morgan-Short (2004) found a lack of a role of EI in PI, and therefore argued that EI may not be a necessary component for PI. Or, as Doughty (2004) put it, the inclusion could be superfluous when one wants to draw attention to form.…”
Section: Discussionmentioning
confidence: 99%
“…Iwashita (2003) indicated a relationship between being exposed to implicit types of corrective feedback and in particular recasts and measurable gains in the acquisition of two grammatical structures in L2 Japanese. Sanz and Morgan-Short (2004) also found that explicit types of corrective feedback may confer no additional advantage over implicit corrective feedback.…”
Section: Introductionmentioning
confidence: 93%
“…Interestingly, the SF condition resulted in a very similar accuracy pattern thus emphasizing the role of accuracy feedback in L2 learning. There is some controversy in the L2 literature regarding what type of feedback is most useful to learners, with some studies showing that more explicit forms of feedback (e.g., correction + metalinguistic explanation) are most effective (R. Ellis et al, 2006;Rosa & Leow, 2004) whereas other studies suggest that any type of feedback or just task-essential practice is sufficient (Ferris & Roberts, 2001;Sanz & Morgan-Short, 2004). It is nevertheless reasonable to conclude that some type of feedback is better than none (but see R. Ellis et al, 2006).…”
Section: Discussionmentioning
confidence: 99%